Motion – Cyclo-oxygenase-2 Selective Nonsteroidal Anti-Inflammatory Drugs are as Safe as Placebo for the Stomach: Arguments Against the Motion - Andreas Maetzel (Canadian Journal of Gastroenterology)
Cyclo-oxygenase (COX) exists in two isoforms, COX-1 and COX-2, that direct the synthesis of prostaglandins, prostacyclin and thromboxane. Traditional nonsteroidal anti-inflammatory drugs (NSAIDs) inhibit both isoenzymes, resulting in damage to the mucosa of the stomach and duodenum, but also in cardioprotection. Selective COX-2 inhibitors are less likely to damage the upper gastrointestinal tract, as has been shown by large, randomized, controlled trials. Specifically, the newer agents are superior to ibuprofen and naproxen in this regard, but celecoxib and diclofenac were not significantly different in patients who were not also taking low-dose acetylsalicylic acid. These studies did not include a placebo arm, however, and controlled comparisons of COX-2 inhibitors with placebo have not enlisted enough subjects to demonstrate conclusively that they are equally safe. Selectivity for the COX-2 isoform affords protection against upper gastrointestinal toxicity possibly at the expense of the cardioprotective effect of traditional NSAIDs. This might explain the higher rate of nonfatal myocardial infarction in patients who aregiven rofecoxib compared with naproxen. A traditional NSAID, combined with either misoprostol or a proton pump inhibitor, is still a suitable alternative to selective COX-2 inhibitors for the treatment of arthritis.